Rupahale śikharoṃ ke sunahare svara : Kumāum kī lokagāthāem evaṃ lokagīta - Joshi, Krishnanand, 1936- (Prakāśa Buka Ḍipo, 1982)
Collection of folk-songs and folk-tales of the Kumaun region of Uttar Pradesh.